Strategi Bertahan Reseller Beteng Trade Center Surakarta di Masa Pandemi COVID-19 - Haniifaa, Haniifaa; Rahman, Abdul; Nurhadi, Nurhadi (International Journal of Demos (IJD), 2022)
AbstractThe Covid-19 pandemi is a condition of the outbreak of the corona virus disease which causes problems in various aspects of life. This makes us required to adapt to the new circumstances it causes. Various government policies and the implementation of health protocols were carried out to break the chain of the spread of Covid-19, which resulted in the closure of the Beteng Trade Center Surakarta shopping center. This study aims to determine the impact of the Covid-19 pandemi and explain the survival strategy of BTC Surakarta resellers during the pandemi. With a qualitative approach, this study discusses the various strategies of resellers in finding ways to survive for their business sustainability with new normal conditions in the midst of the COVID 19 pandemi. This study uses the theory of survival mechanisms developed by James Scott. Data collection was carried out through in-depth interviews, observation, and documentation. The validity of the test data by triangulation of sources. After analyzing the data, the fact finding shows that the reseller's survival strategy during the Covid-19 pandemi includes adjusting income to minimize expenses, increasing income by adding jobs, improving services, and utilizing relationships to work together in business development.Keyword: Strategy, Reseller, Covid-19 Pandemic.Â AbstrakPandemi Covid-19 merupakan kondisi merebaknya wabah corona virus disease yang memunculkan masalah dalam berbagai aspek kehidupan. Hal ini membuat kita dituntut untuk beradaptasi dengan keadaan baru yang ditimbulkannya. Berbagai kebijakan pemerintah dan pemberlakuan protokol kesehatan dilakukan untuk memutus mata rantai penyebaran Covid-19, yang berdampak pada ditutupnya pusat perbelanjaan Beteng Trade Center Surakarta. Penelitian ini bertujuan untuk mengetahui dampak pandemi Covid-19 dan menjelaskan strategi bertahan reseller BTC Surakarta pada masa pandemi. Dengan pendekatan kualitatif, studi ini membahas berbagai strategi para reseller dalam mencari cara bertahan untuk keberlanjutan bisnisnya dengan keadaan new normal di tengah pandemi COVID 19. Studi ini menggunakan teori mekanisme survival yang dikembangkan oleh James Scott. Pengumpulan data yang dilakukan melalui wawancara mendalam, observasi, dan dokumentasi. Validitas data uji dengan triangulasi sumber. Setelah proses menganalisis data, temuan fakta menunjukkan bahwa strategi bertahan yang dilakukan reseller pada masa pandemi Covid-19 meliputi penyesuaian pendapatan guna meminimalisir pengeluaran, menambah pendapatan dengan cara menambah pekerjaan, meningkatkan pelayanan, dan memanfaatkan relasi untuk bekerja sama dalam pengembangan bisnis.Kata Kunci : Strategi, Reseller, Pandemi Covid-19.